In-situ generation of MgAl2O4 particles in Al-Mg alloy using H3BO3 addition for grain refinement under ultrasonic treatment. (December 2018) - Raghu, R.; Nampoothiri, Jayakrishnan; Satish Kumar, T.
Highlights: H3 BO3 particles have greater tendency to form in-situ MgAl2 O4 particles in the Al-Mg alloy under ultrasonic treatment. MgAl2 O4 particles possess better lattice matching with aluminium and acts as potential nucleating sites. MgAl2 O4 particles aids in grain refinement of Al-Mg alloy greatly under ultrasonic treatment. Grain refinement is attributed to synergistic effect of cavitation enhanced nucleation and acoustic streaming. Abstract: A novel approach was made for synthesis of in-situ MgAl2 O4 particles in Al-4Mg alloy by addition of H3 BO3 (0–2 wt%) precursor under Ultrasonic Treatment (UT). The synthesized composites were characterized by Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) analysis. An improved reaction of H3 BO3 with aluminium alloy was observed on 5 min UT. Increase in H3 BO3 addition reduces the grain size of the aluminium alloy till 5–6 times although the ultrasonic effect further contributes greatly to the grain refinement by 2–3 times reduction additionally. Substantial grain refinement by UT was elucidated to the cavitation enhanced reaction of H3 BO3 which resulted in the increased number density of MgAl2 O4 particles. Enhanced wettability of the MgAl2 O4 particles under UT makes it as potential heterogeneous nucleation sites of Al.